Promoting Integrated Farming System in integrated watershed management programme - Siddayya, Siddayya; Kumar, U Hemant (Indian Farming, 2017)
Small and Marginal Farmers are not aware of appropriate farmingsystem practices and modern versions of agriculture practices and grass root systems of IWMP are not competent enough to provideappropriate advice and support. These critical issues are to beaddressed by properly educating and capacitating the farming community and by providing handholding support in adaptable and acceptable practices and with appropriate technologies in agriculture and allied activities. This is possible only by bringing on board the institutions which have the competency to do so either directly to the farming community or through trained field level systems.